Antropología e historia en los Andes. A propósito de la introducción a la antropología histórica de Pier P. Viazzo - Arana Bustamante, Luis (2005)
This book review puts in relationship international development of anthropological history with correspondent studies in the Andean area, presenting a few chronological and theoretical points for a historic and theoretical remarks for a history of this field of Andean studies.